Trust (amanah) Management and Accounting Implications - Iwan Triyuwono (The Indonesian Journal of Accounting Research, 2013)
Accounting is actually neither a static nor a homogeneous phenomenon.  Over time, all forms of accounting have changed, repeatedly becoming what they were not.  Based on this understanding, accounting is not thus a homogeneous craft.  This ever-changing forms of accounting exists as the result of that accounting is not a value-free discipline and practice.  Rather, it is a contextual ones.By making use of interpretive way (of Symbolic Interactionism) as an analytical framework, this paper attempt to interpret the existence of accounting in its social, organisational, and religious context.The result of the interpretation gives us an insight that inner character of self plays a very important role in the process of crafting accounting in the context of a social and religious organisation.  We can see that trust management - as a result of inner self interaction - has a unique implication on accounting craft.